Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Fifgroup Cabang Central Remedial Jawa Barat 2 - Zahratulfarhah Zahratulfarhah; Edward Efendi Silalahi; Hasanuddin Hasanuddin (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to measure the influence of workload and work stress on employee performance at PT. FIFGroup Cabang Central Remedial Jawa Barat 2. The population and sample amounted to 41 people or all employees of the billing division at PT. FIFGroup Cabang Central Remedial Jawa Barat 2. The sampling technique used in this research used saturated samples. The data collection tool in this research used a questionnaire with 41 respondents. The design used in this research is testing using SPSS for Windows version 26. The results of this research show that: (1) Workload has a significant effect on Employee Performance, (2) Work Stress has not effect and is not significant on Employee Performance, (3) Workload and Work Stress has a significant effect on Employee Performance at PT. FIFGroup Cabang Central Remedial Jawa Barat 2. This research provides advice to PT. FIFGroup Cabang Central Remedial Jawa Barat 2 to be able to pay more attention to carrying out busy work every day and pay close attention to and maintain work stress conditions experienced by employees so that employee performance increases.